Pestisida Organoklorin pada Aqifer Dangkal di Wilayah Pesisir Kota Semarang - Chrisna Adhi Suryono; Baskoro Rochaddi (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2009)
Studi ini bertujuan untuk menganalisis kondisi fisika-kimiawi dan tingkat kontaminasi pestisida organoklorin dalam aqifer dangkal di wilayah pesisir Kota Semarang.  Sampel airtanah diambil di 10 lokasi di pesisir Semarang, yang mewakili daerah industri, pertanian dan pemukiman.  Hasil penelitian menunjukkan nilai parameter fisika-kimiawi airtanah (pH, suhu, salinitas) mempunyai variasi yang rendah.  Ke 10 sampel yang diamati menunjukan warna, rasa dan bau dalam air sampel.  Hasil rata-rata kandungan heptaclor adalah 0.023-0.055 µg L-1 dan enfrin adalah tidak terdeteksi sampai 0.648 µg L-1.  Hasil perbandingan kandungan pestsida organochlorine dalam aqifer dangkal di pesisir Semarang dengan WHO dan IWQS menunjukan bahwa air pada aqifer di Semarang termasuk terkontaminasi pestisida organochlorine dan membuktikan telah ditemukannya pestisida organochlorine pada aqifer dangkal di wilayah pesisir Kota Semarang.Kata kunci: aqifer dangkal, organochlorin pestisida, wilayah pesisir  The present study was conducted to assess psycho-chemical parameters and the level of organochlorine pesticides contamination in shallow aquifer of Semarang city coastal areas.  Ten samples of groundwater were collected in different sites of Semarang coastal i.e. industrial, agriculture and settlement areas. The results indicated that low variation existed among some physico-chemical parameter (pH, temperature, salinity). In the colors, taste and odor of 10 water sample were also investigated.  Mean values found in positive samples were heptachlor, ranging from 0.023 to 0.055 µg L-1, whereas endrin, ranging from undetected to 0.648 µg L-1. Compare to World Health Organization (WHO) limits and Indonesian Drinking and Domestic Water Quality Standard for Ground Water (IWQS) showed that this study proved the presence of organochlorine pesticides contamination of some shallow aquifer supplies in the coastal areas of Semarang city. Key  words : shallow aquifer, organochlorine pesticides, coastal area